3.17 Geophysical survey at Sand, Applecross (Scottish Archaeological Internet Reports, 2009)
While geophysical survey techniques were relatively unproductive at Sand in defining the extent of the midden, there is clear potential to explore further the application of these techniques prior to excavation at other midden sites. This research is needed to determine the character of geophysical responses and to assess the suitability of these techniques for discerning the extent of shell midden deposits. In this way, not only is the suite of non-destructive archaeological techniques for Mesolithic research extended, but also possible later events can be highlighted.